Acute and long-term side-effects of radiotherapy: biological basis and clinical relevance ; with 47 tables - Hinkelbein, Wolfgang; Bruggmoser, Gregor; Frommhold, Hermann; Wannenmacher, Michael (Springer, 1993)
Biologists and radiotherapists present their experimental work and clinical data in the field of radiation injuries of normal tissues and organs. Particular regard is payed to the relevance of biological mechanisms in clinical situations. Principles of radiation damage and combined treatment toxicity in radio-chemotherapy are being explained. The main topics discussed are the importance of microvasculature, time, doseand fractionation and factors modifying clinical radioresponse for early andlate radiation effects. Tissues and organs considered in this volume are mucosa and skin, lung and heart, bladder and muscle, CNS and eye. Special problems of pediatric radiotherapy, TBI, IORT and second malignacies are also mentioned
Keywords: Konferenzschrift -- 1991 -- Freiburg, Breisgau; Strahlenbiologie; Strahlenschaden; Strahlentherapie